Limnological parameters in Sôya Coats lakes between the 53rd and 55th Japanese Antarctic Research Expeditions in 2012–2014 —Long-term monitoring study— - KUDOH, Sakae; TANABE, Yukiko (2016)
P(論文) Fig. 1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v004/nipr_parc_362_0014.docx departmental bulletin paper